Evaluation of testing quality of psychomotor reaction of basketball players - Muckus, K.; Zdanaviciene, S.; Cizauskas, A. (Education. Physical training. Sport, 2000)
Ground reaction force (dynamogram) is being registered in evaluation of athlete`s psychomotor reaction (PMR) and jump. Various kinematic and dynamic indices, which represent physical characteristics of athletes, are calculated. It is very important to assess information quality and reliability of these testing elements and select optimal testing batches. The aim of this study is to assess quality (information and reliability) of PMR test, which is used for evaluation of athlete`s speed characteristics and motion indices, responsible for formation of separate PMR components. 9 basketball players from LKKA-Atletas team were included in this study. Two tests were performed: (1) maximal up-jump from standing position and (2) PMR (rapid jump). The first test is designed for evaluation of athlete`s strength and other related physical conditions, the second test - for evaluation of PMR components. Squatting, take-off and flight duration, depth of squatting, and speed at the moment of breaking from touch with the platform, height of jump and work performed values are statistically significantly greater in case of maximal jump than in rapid jump. On the other hand, mean force and dynamic force are greater in case of rapid jump. Power values in both cases are similar. We have studied how speed of PMR is influenced by parameters of jump. Correlation between criterion and jump parameter can be used for assessment of information of the test. Overall timing of PMR has a strong positive correlation with squatting phase (r=0.80) and relative power (r=0.75). Latent time of reaction has a good correlation with duration of squatting time (r=0.60) and relative power (r=0.62). Jump parameters have the greatest influence on motion time: strong correlation with duration of squatting (r=0.90), take-off duration (r=0.62), speed during take-off (r=0.87), jump height (r=0.87) and relative power (r=0.76) and has a negative correlation with dynamic force (r=-0.55). Quality of testing is better when batch of tests, composed from several subtests, which can describe testing aspect, are used. It is demonstrated, that test batch with 2 subtests is sufficient. Reliability of indices of rapid jump is good and is between 0.62 and 0.92, except duration of take-off. Reliability coefficient of this index is 0.19. Conclusions: (1) kinematic and dynamic indices of jump from stand position of basketball players depend on motivation: maximal duration of jump, mean force and work performed are greater, and dynamic force is better in rapid jump; (2) indices of PMR depend on jump duration and dynamic force; (3) test batches, combined from derived PMR components, kinematic components are more informative than dinamic components; (4) selected test batches with 2 sub-components are informative enough.